Online Loan Usage Decisions Among Gen Z in Surabaya: The Roles of OJK Regulation, Locus of Control, Perceived Convenience, and Lifestyle - Angelita, Debry Octavia; Wikartika, Ira (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The rapid increase in the use of online lending services among Generation Z Surabaya indicates a socio-economic phenomenon that is important to analyze further. This study aims to examine the effect of understanding OJK regulations, locus of control, perceived ease of use, and lifestyle on the decision to use online loans by Generation Z in Surabaya. The approach used is a quantitative approach with data processing methods using a relationship model between variables. A total of 100 respondents were selected through purposive sampling technique and data collection was conducted through an online questionnaire with a certain rating scale. The results showed that understanding of OJK regulations and locus of control did not play a role in decision making to use online loans. In contrast, perceived ease of use and lifestyle influence the decision. The findings provide important insights for policy makers, fintech service providers, and the general public in encouraging wiser and more responsible use of online loans.